Dancing is Thinking for Children: Working Memory, Inhibition, and Mental Flexibility - Siti Syarah, Erie; Sumantri, Mohamad Syarif; Rahmawati, Yuli; Jalal, Fasli; Yetti, Elindra (International Electronic Journal of Elementary Education, 2022)
Sharpening working memory skills, inhibition, and mental flexibility of children in many studies have proven school readiness and long-term academic success. The aim of this research is to determine the impact of dancing and listening to music on children's executive functions using the interpretive paradigm with a qualitative case study method. The respondents were seven parents of children aged between 7-8 years. This study used online interviews for the data collection. A typological analysis of qualitative data acquired during the COVID-19 pandemic in the dimensions of working memory, inhibition, and mental flexibility was used to categorize how children's executive functioning might develop in parental care. Several typologies were identified, giving rise to three ideal typologies as a result of the analysis of research questions. Firstly, it is important to develop children's working memory through different new strategies (typology 1); secondly, positive reinforcement was the strongest factor in inhibition development (typology 2); and finally, dancing with music as a support for mental development and development of thinking (typology 3). The research outcomes require increasing adults’ abilities around children to manage diverse learning stimuli and integrate art in them to build working memory, inhibition, and ideal mental flexibility of children.